Does non-invasive brain stimulation applied over the dorsolateral prefrontal cortex non-specifically influence mood and emotional processing in healthy individuals? - Mondino, Marine; Thiffault, François; Fecteau, Shirley (Frontiers in Cellular Neuroscience, 2015)
The dorsolateral prefrontal cortex (DLPFC) is often targeted with non-invasive brain stimulation (NIBS) to modulate in vivo human behaviors. This brain region plays a key role in mood, emotional processing, and attentional processing of emotional information. In this article, we ask the question: when we target the DLPFC with NIBS, do we modulate these processes altogether, non-specifically, or can we modulate them selectively? We thus review articles investigating the effects of NIBS applied over the DLPFC on mood, emotional processing, and attentional processing of emotional stimuli in healthy subjects. We discuss that NIBS over the DLPFC can modulate emotional processing and attentional processing of emotional stimuli, without specifically influencing mood. Indeed, there seems to be a lack of evidence that NIBS over the DLPFC influences mood in healthy individuals. Finally, there appears to be a hemispheric lateralization: when applied over the left DLPFC, NIBS improved processing of positive stimuli and reduced selective attention for stimuli expressing anger, whereas when applied over the right DLPFC, it increased selective attention for stimuli expressing anger.